Tasawuf Transformatif Muhammad Zuhri Solusi Problematika Masyarakat Modern - Rahmad Yulianto (Al Hikmah, 2015)
This article discusses the relevance between Sufism and modernity in the perspective Muhammad Zuhri. This study concludes that transformative Sufism which has been initiated by Zuhri is a sort of Sufism which is grounded to the spirit and values of the fundamental teachings of Sufism, shown in accordance with the context of its time, and discussed with the problems of human beings in dealing with the dynamics of life. Modern life has led to the problem of alienation. Of course, the alienation does not merely occur within individual dimensions (self-consciousness) of human (alienation of consciousness), but it also occurs in their relationship to the nature (ecological alienation), and the relationship among human beings (social alienation). The point of relevance is how the human are subsequently able to build their self-consciousness toward the universe and their human brothers. Such awareness is then contextualized into the dimensions of the problems of modern man. The contextualization of this Sufi teaching makes the transformative Sufism not only actual, but also relevant in order to “liberate” the modern man from entanglement of various problems they deal with. The spirit of Sufism brought by Zuhri seems to be laden with social actions and communal aspects.